Disney's Tarzan - Disney, Walt (New York Golden Books, 1999)
Tarzan, orphaned as a baby and raised by the great ape Kala, must decide, with the arrival of Jane Porter, whether he belongs with humans or apes.
Keywords: feral children -- apes -- jungles -- Africa